Effectiveness of Digital-Based Insurance Learning in Enhancing Risk Literacy among Indonesian Society - Dyah Prita Anggraini; Dhea Ekaputri; Dede Latipah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study investigates the effectiveness of digital-based insurance learning in enhancing risk literacy among Indonesian society. Risk literacy is a critical component of financial literacy that enables individuals to understand uncertainty, evaluate potential risks, and make informed financial decisions. However, the level of public understanding of risk and insurance remains relatively low, highlighting the need for innovative and accessible educational approaches.This research adopts a quantitative approach using a quasi-experimental design with pre-test and post-test measurements. Data were collected from 120 participants who engaged in digital learning modules consisting of interactive videos, simulations, and case-based exercises related to insurance and risk management. Statistical analysis, including paired sample t-tests and regression analysis, was employed to assess the effectiveness of the intervention.The results indicate a significant improvement in participants’ risk literacy, as reflected by higher post-test scores compared to pre-test results. Furthermore, digital learning engagement was found to have a positive and significant influence on learning outcomes. These findings demonstrate that digital-based insurance learning is an effective and scalable strategy for improving public understanding of risk and insurance concepts.This study contributes to the development of an integrated framework combining digital learning, insurance education, and risk literacy. Practically, the findings provide insights for policymakers and educators in designing technology-driven educational programs to enhance financial literacy and risk awareness in Indonesia.